Merawat Persatuan Indonesia Dengan Lima Prinsip Cinta Tanah Air Perspektif Syaikh Kholil Bangkalan - Rifqi Muhammad; Gustina Gustina (Inovasi-Jurnal Diklat Keagamaan, 2022)
This study attempts to connect the precepts of Indonesian unity with the love of the homeland from the perspective of Sheikh Kholil Bangkalan. This study aims to describe the five principles of love for the homeland from the perspective of Shaykh Kholil Bangkalan that can maintain the unity of Indonesia. The procedure used is a qualitative descriptive analysis method with the aim of analyzing the literature and data sources. The results of the study found, namely: 1) Caring for Indonesian Unity by Defending the Homeland Either Through Words or Deeds; 2) Caring for Indonesian Unity by Facing or Combating Anything That Causes Disabilities in State Security and Safety; 3) Caring for Indonesian Unity by Educating Santri and Children to Appreciate the Great Values ​​of the Homeland; 4) Caring for Indonesian Unity by maintaining the harmony of the members or residents and instilling brotherhood; 5) Caring for Indonesian Unity by Creating and Providing Awareness to Students about the Responsibility to Manage Resources. Maintaining the unity of Indonesia by practicing the five principles of love for the homeland from the perspective of Sheikh Kholil Bangkalan can be applied in families, communities, schools, Islamic boarding schools, campuses, and all fields of religious, national and state life. The Indonesian government can make the results of this study a reference for making policies, especially in the field of education to be implemented in schools, Islamic boarding schools, campuses.